2014
DOI: 10.1016/j.sbspro.2014.09.191
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Self-leadership Characteristics of Football Coaches

Abstract: 166 football coaches in the province of Mugla, who participated in the 2014 Mugla SitkiKocman University,Turkish Football Federation (TFF), Turkish Football Coaches Association (TFCA) regional development Seminar organized by TFCA every two years and voluntarily participated in the present research form the research sample.Self-Leadership Questionnaire-SLQ developed by Anderson and Prussia (1997), and personal information form prepared in accordance with the purpose of the present research were used as data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Active participation is not limited to the training session. The athlete pays attention to factors that will affect his performance even out of the coach's supervision by acting with conscientiousness (Bompa, 2001;Bayansalduz, 2012;2014).…”
Section: Introductionmentioning
confidence: 99%
“…Active participation is not limited to the training session. The athlete pays attention to factors that will affect his performance even out of the coach's supervision by acting with conscientiousness (Bompa, 2001;Bayansalduz, 2012;2014).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the findings also showed that professors who with having more than 10 years' experience showed a difference in their self-leadership strategies. Research was conducted, which showed that self-leadership was present more in a faculty that had more experience (Bayansalduz et al, 2014). This is another contradictory finding that might be due to the factor of privileges.…”
Section: Research Question 1 What Is the Link Between Tafila Technical University Faculty' Self-leadership Techniques And Work Motivationmentioning
confidence: 99%
“…On the contrary, "Management" in the current time is an advanced phenomenon within the complex of activities that emerged in the recent era. Also, it is the behavior of the world, whose focus is work, as a model person who is respected as a "manager" (M. Bayansalduz., Afyon, Kepoglu, Dalli, & Mulazimoglu, 2014;Bingol & Bayansalduz, 2016;Can, Soyer, & Bayansalduz, 2009). Leadership is the behavior of an individual who manages the activities of the group to achieve a common goal (Hemphill & Coons, 1957).…”
Section: Introductionmentioning
confidence: 99%